Analysis of Security and Safety of Tourists at Waterfalls in Gianyar Regency - Cokorda Istri Dharmayanti; Agnes Ayu Biomi; Marniati Marniati (Universitas Ibn Khaldun Bogor, 2023)
Background: Nature tourism is in great demand because it offers a different sensation, one of which is waterfalls. Waterfall natural tourism has experienced very rapid development in various places in the province of Bali, one of which is the waterfall in Gianyar district. However, in its development, it has not been balanced with security and safety standards according to the rules that have been set. From the pre-research conducted by the researchers, there were still several incidents at waterfall destinations. There are no handrails on the stairs, the position of the road/stairs is steep and there are no warning signs. Therefore, it is necessary to analyze security and safety so that the researcher raises the title